2012
DOI: 10.1364/oe.20.023944
|View full text |Cite
|
Sign up to set email alerts
|

A 25-mm diameter probe for photoacoustic and ultrasonic endoscopy

Abstract: Abstract:We have created a 2.5-mm outer diameter integrated photoacoustic and ultrasonic mini-probe which can be inserted into a standard video endoscope's instrument channel. A small-diameter focused ultrasonic transducer made of PMN-PT provides adequate signal sensitivity, and enables miniaturization of the probe. Additionally, this new endoscopic probe utilizes the same scanning mirror and micromotor-based built-in actuator described in our previous reports; however, the length of the rigid distal section o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
125
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 48 publications
(53 reference statements)
0
125
0
Order By: Relevance
“…Real in vivo photoacoustic endoscopy imaging was accomplished only recently. 227 Despite these challenges, a few designs of combined OCT/photoacoustic endoscopes have been tested, as are shown in Figs. 15 and 16.…”
Section: Implementations Of Dual-modality Oct/photoacoustic Imaging Smentioning
confidence: 99%
“…Real in vivo photoacoustic endoscopy imaging was accomplished only recently. 227 Despite these challenges, a few designs of combined OCT/photoacoustic endoscopes have been tested, as are shown in Figs. 15 and 16.…”
Section: Implementations Of Dual-modality Oct/photoacoustic Imaging Smentioning
confidence: 99%
“…Our main interest is to adapt the PAI system for the endoscopic scanning in the cervical canal. The endoscopic photoacoustics has always been a main branch in the field of photoacoustic research, which has already been demonstrated in the imaging of vascular and esophagus [33,34]. Small endoscopic photoacoustic catheter with a diameter of 2.5 mm has been reported [34].…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic photoacoustics has always been a main branch in the field of photoacoustic research, which has already been demonstrated in the imaging of vascular and esophagus [33,34]. Small endoscopic photoacoustic catheter with a diameter of 2.5 mm has been reported [34]. Because the majority of the patients with CC are women who have had babies, their cervical canals can be expanded easily.…”
Section: Discussionmentioning
confidence: 99%
“…Fully encapsulated AR-PAM endoscopes have been demonstrated by Yang et al [17,18] using a single mode fiber and an actuation system for the beam steering. Recently OR-PAM images have been acquired by the same group using a device with an outer diameter of 3.4 mm and a lateral resolution of 9.2 μm [19].…”
Section: Introductionmentioning
confidence: 99%